Guided assembly of cancer ellipsoid on suspended hydrogel microfibers estimates multi-cellular traction force. (10th March 2021) - Lee, Cheng-Tai; Gill, Elisabeth L; Wang, Wenyu; Gerigk, Magda; Terentjev, Eugene M; Shery Huang, Yan Yan
Abstract: Three-dimensional (3D) multi-cellular aggregates hold important applications in tissue engineering and in vitro biological modeling. Probing the intrinsic forces generated during the aggregation process, could open up new possibilities in advancing the discovery of tissue mechanics-based biomarkers. We use individually suspended, and tethered gelatin hydrogel microfibers to guide multicellular aggregation of brain cancer cells (glioblastoma cell line, U87), forming characteristic cancer 'ellipsoids'. Over a culture period of up to 13 days, U87 aggregates evolve from a flexible cell string with cell coverage following the relaxed and curly fiber contour; to a distinct ellipsoid-on-string morphology, where the fiber segment connecting the ellipsoid poles become taut. Fluorescence imaging revealed the fiber segment embedded within the ellipsoidal aggregate to exhibit a morphological transition analogous to filament buckling under a compressive force. By treating the multicellular aggregate as an effective elastic medium where the microfiber is embedded, we applied a filament post-buckling theory to model the fiber morphology, deducing the apparent elasticity of the cancer ellipsoid medium, as well as the collective traction force inherent in the aggregation process.